Implications of Constitutional Court Decisions on The Protection of The Voting Rights of Persons with Mental Disabilities: (Study in Bali Province and Special Region of Yogyakarta) - Syafi'ie, M.; Heryansyah, Despan; Reza, Fatma; Dey, Nabhojit (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
Normatively, the right to vote for persons with mental disabilities in elections was not fully recognized in Article 57 paragraph (3) of Law no. 8 of 2015. This law stipulates that one of the conditions for voters in elections is "not having mental/memory problems". This phrase interpreted broadly that all persons with mental disabilities are not entitled to the right to vote. This phrase was then tested by the Constitutional Court, whereupon the Constitutional Court issued Decision No. 135/PUU-VIII-2015 which substantially invalidates the phraselet's talkand granting the right to vote in general elections for persons with mental disabilities. This decision is considered a progressive leap taken by the Constitutional Court to ensure fair elections, because people with mental disabilities are not the same as people with schizophrenia, with a more humane approach and adequate medicine, people with mental disabilities are the same as people without mental disabilities. Therefore, the author is interested in seeing more deeply how this Constitutional Court Decision can fulfill the right to vote for persons with disabilities. This research is a type of non-doctrinal research that uses both primary and secondary data. The areas that are used as research objects are the provinces of Bali and DIY. The results of the study show that from a quantitative aspect there has been an increase in the participation of voters with mental disabilities. However, the implementation of the Constitutional Court's decision by the election organizers is also still encountering various obstacles, both administration, infrastructure, and services